2014
DOI: 10.1002/cbic.201400032
|View full text |Cite
|
Sign up to set email alerts
|

An Expanded Set of Fluorogenic Sulfatase Activity Probes

Abstract: Fluorogenic probes that are activated by an enzymatic transformation are ideally suited for profiling enzyme activities in biological systems. Here, we describe two fluorogenic enzyme probes, 3-O-methylfluorescein-sulfate and resorufin-sulfate, that can be used to detect sulfatases in mycobacterial lysates. Both probes were validated with a set of commercial sulfatases and used to reveal species specific sulfatase banding patterns in a gel-resolved assay of mycobacterial lysates. The fluorogenic probes describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 36 publications
2
25
0
Order By: Relevance
“…[10] Furthermore, we recently applied fluorogenic probes to examine mycobacterial sulfatases in a protein gel-based assay format. [11, 12] We found that although most mycobacterial species, including M. tuberculosis , could hydrolyze sulfated fluorophores, the pattern of sulfatase activity varied from one species to another.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…[10] Furthermore, we recently applied fluorogenic probes to examine mycobacterial sulfatases in a protein gel-based assay format. [11, 12] We found that although most mycobacterial species, including M. tuberculosis , could hydrolyze sulfated fluorophores, the pattern of sulfatase activity varied from one species to another.…”
mentioning
confidence: 98%
“…[1622] Fluorogenic enzyme probes could directly detect enzyme activities in intact organisms [9, 10] or in protein gel-resolved lysates without the need for isolated enzyme. [11, 12, 23] …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Sulfatase from Helix pomatia  (S9626) was reported to show activity at pH 5.0 and 37 °C [7], [8] (Fig. 5).
Fig.
…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 96%
“…Activitybased probes have been designed to detect a number of bacterial proteins, such as sulfatases 85,86 , serine proteases 87 , the cell wall biosynthetic protein MurA 88 , glycoside hydrolases 89 , redox-sensitive proteins 90,91 and histidine kinases 92 ; however, most of these probes have been used only in gel-based analyses. One additional strategy that has been applied to bacterial imaging is the use of a probe that becomes fluorescent upon turnover by nitroreductase.…”
Section: Additional Small-molecule Probesmentioning
confidence: 99%